(untitled) (Cadernos de Linguagem e Sociedade, 2010)
In this paper on literacy in the community, I argue for the gains of research in discourse, particularly Critical Discourse Analysis, in combination with an ethnographic approach. If for one hand Discourse Analysis proposes to be a tool to make clear the ideological investments in textual materiality (Fairclough, 1992), on the other hand such investment is partially raised in social practices and their networks, of which it is a part. From the relation of discourse with other aspects of social practice, such as participant’s systems of values, beliefs and knowledge in the events, upsurges the need to incorporate an ethnographic approach, as much as a mode of knowledge production as a set of techniques implemented to generate data on those aspects of social practice.